Severe Encephalitis in Infant with COVID-19: A Case Report - Sofijanova, Aspazija; Bojadzieva, Sonja; Duma, Filip; Superlishka, Elizabeta; Murtezani, Avdi; Jordanova, Olivera (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Encephalitis is a serious condition that contains neurological dysfunction cause by inflammation of the brain tissue. Etiological factors for the occurrence of this condition include infectious and non-infectious causes. CASE REPORT: We are presented 9-month-old infant referred to our clinic in convulsive status, fever, and disturbed consciousness. From anamnestic information, the infant has been febrile for 2 days with profuse vomiting initiating just before admission at the clinic. At the moment of admission in the clinic, the infant looked intoxicated with generalized tonic-clonic seizures, with shortness of breath and fever with a weakened reaction to painful stimuli. It was admitted in the Isolation Unit by the protocol of the clinic. Laboratory investigations were done. Due to the persistence of convulsive status, a computed tomography scan of the brain was performed with the finding of enlargement of the lateral ventricles, with intraventricular masses and pronounced internal hydrocephalus. The results of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) from the infant were positive as well as the grandmother. The infant was intubated immediately and put on mechanical ventilation SIPPV. CONCLUSION: Our case report could suggest that SARS-CoV-2 infection may cause severe clinical symptoms, neurological manifestations, and encephalitis in infants.